2018
DOI: 10.1038/s41598-018-25041-3
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of UV Second-Harmonic Radiation at Nonlinear Interfaces with Discontinuous Second-order Susceptibilities

Abstract: We investigate the generation of ultraviolet (UV) second-harmonic radiation at the boundary of a UV transparent crystal, which is derived from the automatic partial phase matching of the incident wave and the total internal reflection. By adhering to another UV non-transparent crystal with a larger second-order nonlinear coefficient χ(2), a nonlinear interface with large disparity in χ(2) is formed and the enhancement of UV second-harmonic radiation is observed experimentally. The intensity of enhanced second … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…In [27] it is theoretically shown that from topological edge states, harmonics can be 14-orders of magnitude more efficiently generated than from bulk, what may be applicable to surfaces. An experimental study [28] reports that from the interface between two materials the second harmonic can be more efficiently generated. High harmonics on a surface in reflection geometry have also been generated [29].…”
Section: Resultsmentioning
confidence: 99%
“…In [27] it is theoretically shown that from topological edge states, harmonics can be 14-orders of magnitude more efficiently generated than from bulk, what may be applicable to surfaces. An experimental study [28] reports that from the interface between two materials the second harmonic can be more efficiently generated. High harmonics on a surface in reflection geometry have also been generated [29].…”
Section: Resultsmentioning
confidence: 99%